2013
DOI: 10.1007/s11605-012-1996-1
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Modulation by Methionine Deficiency Attenuates the Potential for Gastric Cancer Cell Dissemination

Abstract: In summary, we have provided evidence that a methionine-deficient diet modulates the growth of gastric tumor cells and in vitro deficiency of methionine increased apoptosis and decreased cellular adhesion and migration associated to epigenetic change of E-cadherin gene, in vivo and in vitro.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 25 publications
0
11
0
1
Order By: Relevance
“…Several studies have shown that human tumors, including those derived from the nervous system such as glioblastoma, medulloblastoma, neuroblastoma and gastric cancer are much more sensitive than normal tissues to L‐methionine starvation and L‐methionine is also required for polymanine synthesis (Kreis and Goodenow ; Thomas and Thomas ; Graziosi et al . ; Stone et al . ).…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have shown that human tumors, including those derived from the nervous system such as glioblastoma, medulloblastoma, neuroblastoma and gastric cancer are much more sensitive than normal tissues to L‐methionine starvation and L‐methionine is also required for polymanine synthesis (Kreis and Goodenow ; Thomas and Thomas ; Graziosi et al . ; Stone et al . ).…”
Section: Resultsmentioning
confidence: 99%
“…Рацион с дефицитом метионина тормозил рост опухоли в модели перитонеального карциноматоза после трансплантации клеток рака желудка MNK45 и MNK74 мышам NOD-SCID. В каче-стве одной из причин полученного эффекта авторы считают угнетение метилирования промотора гена Е-кадгерина [90].…”
Section: возможность использования рациона со сниженным содержанием мunclassified
“…Nonetheless, a study suggests that dietary methionine supplementation in rodents significantly increases methylation levels and prevents gamma-radiation-induced-global DNA hypomethylation [45]. A methionine-deficient diet modulates the growth of gastric tumor cells and in vitro deficiency of methionine increases apoptosis rate and decreases cellular adhesion and migration associated with decreased E-cadherin promoter methylation and increased gene expression, in vitro and in vivo [47]. A methionine-deficient diet modulates the growth of gastric tumor cells and in vitro deficiency of methionine increases apoptosis rate and decreases cellular adhesion and migration associated with decreased E-cadherin promoter methylation and increased gene expression, in vitro and in vivo [47].…”
Section: Methioninementioning
confidence: 99%